Persons in communion : an essay on Trinitarian description and human participation, with special reference to volume one of Karl Barth's Church dogmatics /: an essay on Trinitarian description and human participation, with special reference to volume one of Karl Barth's Church dogmatics. (1996) - Unknown
No abstract available